The Influence of Mobile Banking Attributes on Cashless Society through Adaptive Anthropomorphism and Task-Fit Technology - Wirabuana, Satria; Ariadi, Gede (Bina Nusantara University, 2025)
The research aimed to analyze the role of adaptive anthropomorphism and Task-Fit Technology (TFT) in mediating the relationship between performance expectancy, effort expectancy, perceived security, and a cashless society among traditional market traders. The research procedures applied a quantitative design, and the sample population consisted of 279 traditional market traders who had utilized mobile banking services. The data obtained were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to measure the structural relationships. Smart-PLS 3 was utilized as the analytical tool, following a two-stage process to examine data and assess the influence and significance of mediating variables. The results show the benefits of integrating Mobile Banking with the Unified Theory of Acceptance and Use of Technology (UTAUT) and Task-Fit Technology (TFT), offering scientific explanations and empirical evidence based on customer experiences in financial transactions. Adaptive anthropomorphism serves as a mediating factor, bridging the relationship between facilitating conditions, perceived security, perceived trust, and the adoption of a cashless society. In addition, TFT mediates the connection between effort expectancy, perceived security, perceived trust, and the adoption of a cashless society within the context of mobile banking services. These results could be helpful for banking management because facilitating conditions positively encourages the use of non-cash payments in the market between merchants and consumers where proof of payment is represented through human-like voice interaction.